Facing the Other: Representations of Postcolonial Childhood Trauma in Arundhati Roy’s God of Small Things and Amitav Ghosh’s The Shadow Lines - Sarwar, Batool (Spectrum, 2022)
Recent developments in the fields of postcolonial and trauma studies have focused on how there can be a significant interrelationship in the frameworks deployed to investigate the formation of identities in postcolonial subjects. The emphasis on anxiety and fractured subjectivities that inform discussions of postcolonial identity can also be conceptualized in terms of traumatic interventions at crucial moments in the development of selfhood. This paper will contend that though childhood is one of the most crucial times when the formative influences for the development of personality are inscribed onto the psyche of the individual, very little attention has been paid to children as a separate group in theorizations of postcolonial identity. This paper will attempt to use notions such as ‘insidious trauma’ inflicted by entanglements with British culture and education as a critical lens for the study of the formation of identity in the lives of the protagonists of two novels by two Indian authors. It will also engage with the personal trauma inflicted on these children by political upheavals as well as by the trauma caused by adult figures in their Anglophile families. This paper will therefore show that the complex and multilayered trauma suffered by postcolonial children has a profound impact on their adult lives, leaving them permanently scarred and that any attempts at resistance by the victims of such trauma are failures or at best only partially successful. Spectrum, Volume 16, June 2021: 136-147